SIGNIFICANCE OF ADENOSINE DEAMINASE IN DIAGNOSING TUBERCULOUS PLEURISY : ADENOSINE DEAMINASE IN DIAGNOSIS OF TUBERCULOUS PLEURISY - Janković, Jelena; Ilić, Branislav; Jandrić, Aleksandar (Srpski medicinski časopis Lekarske komore, 2023)
Tuberculous pleurisy (TP) is one of the most common extra-pulmonary tuberculosis forms. Tuberculous pleurisy occurs when Mycobacterium tuberculosis antigen is released from a ruptured caseous focus into the pleural space causing hyperinflammatory response with a rapid influx of lymphocytes. Acid-fast bacilli (AFB) staining, cultures and pathohistological biopsy finding are positive in most patients only in less than 10% of samples. Culture results take about 6-8 weeks which delays the diagnosis. A problem also occurs in the differentiation of effusions with lymphocytic predominance. Adenosine deaminase (ADA) is a biochemical marker with high sensitivity and specificity and is considered a gold standard within biomarkers when it comes to diagnosing TP. Using an algorithm for the values of ADA above or below 40 U/L we can distinguish this type of effusion from other types. ADA in pleural punctate is a fast, efficient, and economical way for clarifying the etiology of a pleural effusion such as tuberculous pleurisy and treatment response during the follow up period.
Keywords: Adenosine deaminase; biomarkers; pleural effusion; tuberculosis